U. S. - Japan relation in a changing world (Brookings Institution Press, 2002)
This new book evaluates the changing relationship between the two great powers, providing in-depth analysis on a variety of topics. It scrutinizes the historical context, providing the reader with predictive tools for understanding events as they unfold. Instead of looking at the U.S.-Japan relationship one issue at a time, this book examines specific trends and then analyzes how these trends affect the relationship as a whole.